Distribución geográfica y estado de conservación del cactus endémico Austrocylindropuntia pachypus y nuevos registros para el sur del Perú - Taquiri Yanqui, Willinton (2024)
Austrocylindropuntia pachypus (K.Schum.) Backeb. it is an endemic cactus whose distribution was restricted to the western slopes of La Libertad, Ancash, Lima; and based on botanical expeditions through the Andean foothills of Ica, new records are reported with reduced populations of A. pachypus, which makes it possible to extend its known distribution to southern Peru by more than 260 km; in addition, based on 35 georeferenced records, information is presented on their locations, populations, potential distribution, habitats, threats, and the conservation status was analyzed. The potential distribution model shows high predictive or suitability levels with AUC values = 0.96 based on seven climatic variables (Bio17, Bio2 and Bio7 being the ones with the greatest contribution), with the departments with the highest suitability values being: Lima, Ancash, Lambayeque, La Libertad, Huancavelica and Ica. The localities where they are most concentrated and in turn are seriously disturbed by anthropogenic activities are the valleys of the Chillon river (Santa Rosa de Quives - Canta) and Rimac (Santa Eulalia - Huarochiri) in Lima; due to this, almost 70% of the records and populations of A. pachypus are threatened by mining rights, hydrocarbon extraction, overgrazing, and urban or agricultural expansion, which increases the fragmentation of their habitats and isolates the few populations of A. pachypus, therefore, it is proposed to categorize this endemic cactus as Endangered (EN).